ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH PROPINSI SEINDONESIA - Retnowati Dwijayanti; Rusherlistyanti . (Jurnal Ekonomi Dan Bisnis, 2015)
This study aims at determining the comparative analysis of the financial performance of the provincialgovernments in Indonesia and determines whether there are differences in the financial performance of theprovincial governments in Indonesia based on self-sufficiency ratio, the ratio of PAD effectiveness, efficiencyratios, activity ratios, and growth ratios.The data used in this study is a secondary data is the 2008-2010 Regional Financial Statements at 33provinces in Indonesia. The data is taken from the official website www.djpk.depkeu.go.id General Directorof Fiscal Balance and the Central Bureau of Statistics (BPS). Analysis techniques used in this research is theanalysis of financial ratios and analysis of financial performance of the different test, if the data werenormally distributed and are eligible One Way ANOVA test, then the researcher would use One Way ANOVAtest. Conversely, if the data are not normally distributed, the researcher would use the Kruskal Wallis test.The analysis revealed comparative financial performance of provincial governments in Indonesia 2008-2010period based on ratio analysis rated the independence of East Java first. Effectiveness ra tio analysis resultsPAD rated first province of West Papua. The results of the efficiency ratio analysis Bali Province rated first.The results of the activity ratio analysis routine and development expenditures West Sulawesi prioritizedevelopment expenditure compared to regular shopping. Results of analysis of 2009 growth rate PADprovince in Indonesia has decreased from the previous year. Earnings growth ratio DI Jogjakarta andGorontalo Province has increased from 2008-2010, instead of West Sumatra, West Nusa Tenggara, SouthKalimantan, Southeast Sulawesi and West Papua and other provinces decreased fluctuate. Routineexpenditure growth ratio Bengkulu province and Jakarta has increased from 2008-2010, instead of NorthSumatra, Riau, Jambi, Bangka Belitung, West Nusa Tenggara, South Kalimantan, Central Sulawesi, Malukuand Papua and other provinces decreased fluctuate. The ratio of development expenditure growth Acehprovince, Jambi, Central Java, Yogyakarta, West Kalimantan, Central Kalimantan, Central Sulawesi, WestSulawesi and West Papua has increased from 2008-2010, instead of North Sumatra, Lampung, East NusaTenggara, South Sulawesi and Papua and other provinces decreased fluctuate. Kruskal Wallis test resultsdifferent that there is no significant difference in the financial performance of the provincial government asseen from the 2008-2010 period Indonesi efficiency ratio, revenue growth, revenue growth, growth in routineexpenditure and development expenditure growth, so that the others there is a difference. Keywords: Financial Performance, Independence, PAD Effectiveness,  Efficiency, Activity, Growth.